RA V11 N1, Message from the Editor in Chief (January - April 2021) - Castro Borges, Pedro (Revista ALCONPAT, 2021)
JOURNAL OF THE LATIN-AMERICAN ASSOCIATION OF QUALITY CONTROL, PATHOLOGY AND RECOVERY OF CONSTRUCTION http://www.revistaalconpat.org With great satisfaction, we present the first issue of the eleventh year of the ALCONPAT Journal. The objective of the Journal is the publication of contributions on basic or applied research directly related to solving problems about quality control, pathology and recovery of constructions, with related case studies being welcome in these areas. This V11N1 edition begins with a work from Brazil, where Hygor Thairony Parreira Vilela and colleagues evaluate the effectiveness of the use of different levels of crystallizing additive to prevent the alkali-aggregate reaction in mortars. The analysis was carried out by means of expansion tests of mortar bars by the accelerated method, in parallel with tests of mechanical resistance, capillarity, porosity and percentage of voids. It was observed that the presence of alkaline products in the additive composition significantly increased the initial expansions within the first week. Regarding the results of mechanical resistance, water absorption and voids, the product was satisfactory, improving the properties of the mortars. In general, the results attest to the effectiveness of the additive in sealing voids and pores, but not in inhibiting the alkali-aggregate reaction. In the second work, Alejandro Flores-Nicolás and colleagues from Mexico evaluate the effect of corrosion of reinforced concrete without and with the addition of low carbon graphite powder. The phase identification processes and the physical-electrochemical properties of the concrete were analyzed by using X-ray diffraction techniques (XRD), scanning electron microscopy (SEM), half-cell potential, electrochemical noise (EN) and resistance to polarization. linear (RPL). The samples were studied for 168 days in saline solution. The results show that when adding graphite powder in an amount of 2.5% by weight of the cement, the resistance to compression was increased compared to the control sample. Electrochemical tests show that the corrosion of reinforcing steel in concrete increased as the level of graphite replacement increased. The third article comes from Brazil, where Renata dos Santos Kimick and colleagues comparatively analyze the waterproofing systems used in the Brazilian market. The products evaluated were asphalt emulsion, acrylic resin and thermoplastic resin. To evaluate the effectiveness of the systems, tightness, absorption by immersion and capillarity tests were carried out, the latter being also analyzed by thermographic images. For the efficiency analysis of the systems, an accelerated aging pattern was adopted, which consisted of alternating the samples in wet and dry cycles. The results indicate a good performance for the studied systems, which in comparison with the non-impermeable series presented lower absorbances (approximately 300%). The accelerated aging test indicated, after 140 days of age, a reduction in the performance of the waterproofed series. In the fourth article from Spain, Pedro Garcés Terradillos and colleagues have studied the feasibility of a combined treatment of electrochemical chloride extraction (ECE) and cathodic protection (CP) in reinforced concrete structures using a conductive cement-graphite paste as anode. It has been proven that the prior application of an electrochemical chloride extraction treatment leads to a greater durability of the anode. It has been shown that, for reinforced concrete structures located in aggressive marine environments, the combination of electrochemical treatments, first ECE to reduce the content of chlorides and then CP to maintain passivation conditions, is capable of providing adequate protection conditions to the reinforcement, provided that the appropriate current density value is applied, in accordance with the average content of chlorides present in reinforced concrete structures. The fifth article, by Rogerio Taygra Vasconcelos Fernandes and colleagues, comes from Brazil; they studied the feasibility of using drones to map and inspect pathological manifestations in asphalt pavements in comparison with the traditional method. Sample plots were established every 20 m, 6 m long, totaling 20 stations, which had their pathological manifestations noted and the Global Severity Index calculated for the study area. The results obtained with the reference and alternative methodologies were compared based on the pathologies identified and the time spent in the surveys. The results demonstrated viability for the use of Drones in the inspection of asphalt pavement pathologies, based on the DNIT 006/2003 - PRO Standard, obtaining results like the traditional methodology with a significant reduction in operating time (33.3%). The sixth work of this issue is written by Carlos Aire and L. Aguilar from Mexico, they evaluate three tests to characterize the behavior of concrete shot with metallic fibers in the primary lining of the tunnel of CDMX metro line 12. Three square panels (UNE 14488-5), three round panels (ASTM C1550) and four cylinders for Barcelona test (UNE 83515) were made. All can be used as quality control methods for fiber-reinforced concretes (FRC) in underground constructions, however, greater variability was found in the results of circular panels, in addition to being the specimens with greater complexity for their elaboration and test. Therefore, the application of the Barcelona test is recommended for quality control on site because it is easier to prepare, handle and execute the sampling and test. In the seventh work, from Brazil, Ramiro Daniel Ballesteros Ruiz and colleagues evaluate the use of unmanned aerial vehicles (UAVs) as a visual tool for the inspection of pathological manifestations on facades through an exploratory study. At present, UAVs are becoming increasingly important in civil construction as a new mechanism for obtaining data and visual inspection, optimizing time. The research strategy considers three different stages: bibliographic review, the experimental procedure and, finally, data processing, with the aim of verifying the feasibility of the inspection procedure. The convenience of using UAV is evident, particularly where access is difficult, which can reduce time, costs and generate greater security, in addition to the 3D reconstruction of the building to be inspected and generate more accurate diagnoses. In the eighth paper, from Spain, Vicente Alegre and S. Villalba discuss the example of a real case in which, on an existing tunnel, a building with fiber optic instrumentation is built that allows the monitoring of the load history of a structure from its installation. To verify that the tunnel is not structurally affected during the construction period, sections of it are instrumented and the microdeformations that occur are measured, which are compared with those of the model. The ovalizations and tensions in the vault have been appreciated during the different phases of the construction process, all of them being below the limit values established in the contingency plan. This technique has made possible to validate the works carried out throughout the process. The last article that closes this issue is written is by Willians Perlley Alexandre da Silva and colleagues from Brazil, who present the use of the thermographic camera integrated in UAV in building inspection processes. The development of this work was based on a systematic review of articles and works related to the subject, investigating the characteristics and operation of thermographic cameras, the use of UAVs and the factors that influence the detection of pathological manifestations. The results allowed to identify the advantages and limitations of the integration of cameras and UAV, demonstrating the viability and effectiveness of the joint use. As a contribution, this work provided the development of a flight protocol that orders the steps and procedures necessary to perform an inspection using the thermal camera integrated in UAV. We are confident that the articles in this issue will constitute an important reference for those readers involved with questions about evaluations and characterizations of materials, elements, and structures. We thank the authors participating in this issue for their willingness and effort to present quality articles and meet the established deadlines. Exactly 10 years ago, in January 2011, we were launching the first issue of the Alconpat Journal (RAV1N1). 10 years away, I must give wide recognition to the original editorial staff and to those who have joined to this initiative that has led us to where we are now. But undoubtedly, the greatest recognition is deserved by our articles´ authors, who have trusted in our journal and invested time, money and effort to publish their research work with us, despite the fact that many of them have had better options in their moment. Finally, our readers, without them we are nobody, a special thanks for reading, downloading, and citing us. Your preference will undoubtedly give us, in a short period of time, opportunities to continue improving through better tools for consultation and indexing. Many, many thanks to all. During 2021 we will celebrate these 10 years with some academic celebratory activities that we will make known in each edition. On behalf of the Editorial Board Pedro Castro Borges Editor in Chief